The relationship between the frequency of cleaning facial skin and the incidence of acne vulgaris - Sulaksono, Nabila; Rizkita, Leonny Dwi; Suryaningsih , Betty Ekawati (Universitas Ahmad Dahlan, 2025)
Acne Vulgaris is a skin infection experienced by almost the entire population in the world. Global Burden of Disease (GBD) in his research, acne vulgaris occurs in around 85% of young to adult individuals aged 12 to 25 years. The main aim of this research is to determine the relationship between frequency of facial cleaning and acne vulgaris in Ahmad Dahlan University Medical Students Class of 2022. This research uses an analytical observational approach with a cross-sectional study approach. Specialist doctors in the field of dermatology examined samples of 94 students to identify acne vulgaris, after tabulation of samples that could be processed as many as 80 student samples. Frequency of facial cleaning was related to facial cleaning behavior as measured using a questionnaire. Demographic data, characteristics of acne vulgaris and frequency of facial cleansing were reported. Data processing uses univariate analysis and bivariate chi-square analysis. Hypothesis testing using the chi-square test with a confidence level of 95% obtained a p-value of 0.000 which is smaller than the significance of 0.05. The frequency of cleaning your face will reduce the occurrence of acne vulgaris or be a treatment to prevent acne vulgaris from occurring. The recommended frequency is 2-3x a day, it doesn't need to be more than 5x a day, because this can cause facial irritation and ultimately acne vulgaris.